2021
DOI: 10.2478/fon-2021-0031
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation and associated factors among students of the Institute of Health in Jimma University, Southwest Ethiopia

Abstract: Objective Despite getting sufficient sleep being one of the most important things that we can do to keep our body and mind healthy, sleep deprivation has become a major public health concern. This study aimed to determine the prevalence of sleep deprivation and its associated factors among students of the Institute of Health in Jimma University. Methods An institution-based cross-sectional study was conducted from April 10 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Electronic device use: If the participant uses/watches at least one of the following: television, computer, tablet or mobile phone in bed before going to sleep. 44 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Electronic device use: If the participant uses/watches at least one of the following: television, computer, tablet or mobile phone in bed before going to sleep. 44 …”
Section: Methodsmentioning
confidence: 99%
“…35 Moreover, poor SQ has been correlated to old age, low economic status, substance use, obesity, use of an electronic device before bedtime, higher risks of contracting COVID-19 at work, workload and job stress. [36][37][38][39][40][41][42][43][44] Given the widespread and harmful consequences of poor SQ, it needs to be a top priority for public and occupational health. As previously stated, a thorough review of the literature revealed that even less is known about the prevalence and factors of poor SQ among academic staff and other university personnel in developing countries including Ethiopia.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…53 Electronic device user Workers who used or viewed at least one of the following: television, computer, tablet or phone in bed before going to sleep in the last month. 54…”
Section: Night Shift Workmentioning
confidence: 99%